Implementation of Docker Platform for Integration Of Thesis Information System And Web-Based Thesis Title Checking Information System In Informatics Study Program - Ryanto, Rizky Adi; Julkarnain, M.; Yuliadi, Yuliadi; Sofya, Nora Dery; Oktavia, Siska Atmawan (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The use of technology-based information systems not only improves operational efficiency but also enriches the learning and teaching experience. In this context, the management of theses, as an essential part of higher education programs, is one area that receives special attention. Based on the results of the observations, the Informatics Study Program registration process and scheduling of proposal seminars and final project trials are currently carried out conventionally. Meanwhile, the Informatics Study Program already has two previous systems, namely the thesis title checking system and the registration system and final project scheduling. However, they still need to be integrated and implemented on the server so the registration process is carried out conventionally. This study uses the Docker platform to discuss integrating the thesis information system and title-checking system in the Informatics Study Program at the Sumbawa University of Technology. The main goal is to improve operational efficiency and user experience, especially for students and teaching staff. This study covers various steps through the Software Development Life Cycle (SDLC) approach and qualitative methods, from analyzing the running system and proposals to implementing Docker as a containerization platform. This integration brings significant changes, uniting the thesis title-checking and registration processes in one integrated platform. The results show increased administrative efficiency, more accessible access, and more focused use. However, this study also encourages further development for system maintenance, data security, and improvements according to user feedback to improve system functionality and resilience in the future.